2021
DOI: 10.1177/03000605211020219
|View full text |Cite
|
Sign up to set email alerts
|

Upper and lower adjacent segment range of motion after fixation of different lumbar spine segments in the goat: an in vitro experiment

Abstract: Objectives The purpose of this study was to examine the biomechanical effects of fixation on range of motion (ROM) in the upper and lower adjacent segments of different lumbar spine segments in a goat spine model. Methods Fifteen goat spine specimens (vertebrae T12–S1) were randomly divided into three groups: A (single-segment fixation), B (double-segment fixation), and C (triple-segment fixation). Motion in different directions was tested using a spinal motion simulation test system with five external loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This can cause not only lateral curvature (or lateral rotation) but also phenomena such as rotation or flexion/extension (FL/EX). Additionally, under an axial rotation, the posterior fixation changes the original rotation centre of the spine, resulting in a difference between the adjacent vertebral bodies and the rotation centre of the vertebral body [ 41 , 42 , 43 , 44 ]. This difference may be accompanied by additional displacements of the vertebral bodies, amplifying the coupling effect during lateral bending or rotation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can cause not only lateral curvature (or lateral rotation) but also phenomena such as rotation or flexion/extension (FL/EX). Additionally, under an axial rotation, the posterior fixation changes the original rotation centre of the spine, resulting in a difference between the adjacent vertebral bodies and the rotation centre of the vertebral body [ 41 , 42 , 43 , 44 ]. This difference may be accompanied by additional displacements of the vertebral bodies, amplifying the coupling effect during lateral bending or rotation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tests were performed recurring to a spine-loading apparatus already described in a previous study (Borrelli et al, 2021) and shown in Figure 1. Briefly, this spineloading apparatus orients the phantom to make the L3 inferior endplate horizontal, consistent with the anatomical orientation of lumbar segment (Wilke et al, 1998), and it allows bending through an eccentric vertical load applied to the cranial vertebra Frontiers in Bioengineering and Biotechnology frontiersin.org with S1 fixed to the machine (Patwardhan et al, 1999;Cripton et al, 2000;Marras et al, 2021;Ou et al, 2021;Garavelli et al, 2022). Thus, the resulting moment of the forces was calculated by assuming a constant arm with respect to the caudal constraint.…”
Section: Testing Apparatus and Testing Proceduresmentioning
confidence: 99%
“… 21 The reasons for such a wide experimental effort are mainly the incidence of clinical problems affecting the spine such as reduced mobility, pain and other pathologies. Some studies, for example, were aimed to establish the loss of mobility which might come as a consequence of vertebral fusions 20 ; other studies were addressed to define specifications for prosthetic implants 28 , 31 or to simulate the outcome of surgery 18 . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%